A synthetic-dynamic method for water solubility measurements in high pressure CO2 using ATR–FTIR spectroscopy - Comak, Gurbuz; Foltran, Stéphanie; Ke, Jie; Pérez, Eduardo; Sánchez-Vicente, Yolanda; George, Michael W.; Poliakoff, Martyn (Elsevier, 2016)
A new synthetic method for studying phase behaviour is described using Attenuated Total Reflection (ATR) spectroscopy. The method has been developed to provide relevant information on the solubility of water in CO2. The dew point of water has been determined at three different pressures, viz. (4.05, 5.05 and 6.03) MPa with mole fractions of water between 0.01 and 0.04. The data obtained fill the gap in the literature in these regions of pressures and temperatures and could be of high importance in the context of Carbon Capture and Storage (CCS) technology. Indeed, the presence of water in the captured CO2 could damage the pipeline used for CO2 transport. Hence, it is very important to have a fully understanding of the behaviour of the (CO2 + H2O) mixtures in wide range of temperature relevant for CCS.